DI AMBANG KEGAIRAHAN DAN KERENTANAN (Fleksibilitas Freelance Industri Kreatif Desain di Yogyakarta) - Hikmawati, Ulfah Nur (Jurnal Studi Pemuda, 2023)
Freelance designers in Yogyakarta can be identified as cognitive workers. They work with critical thinking, creativity, fragmented knowledge, and dependent to technological tools. In addition, they live and work side by side with vulnerabilities. This article aims to explore the dynamics of cognitive work on freelancer design in Yogyakarta. According to the observations of researchers, Yogyakarta is a place that has a distinctive feature in the dynamics of working for freelancer design in Yogyakarta. Especially in relation to their social capabilities in networks. This article also tries to elaborate the desire to work behind the vulnerabilities experienced by freelancer design workers in Yogyakarta. Ethnographic methods and in-depth interviews are utilized to collect data as well as to observe the daily activities of freelancer designers in Yogyakarta. The data was collected for about six months. The findings based on the field research show that freelancer designers in Yogyakarta have to decide between their passion for their work and their vulnerability. These freelancer can work according to their desire and idealism to channel satisfaction and consistency in their work, but they must also deal with panic and uncertainty in their work. So, freelancer design in Yogyakarta has this life flooded with excitement and vulnerability.